Drain Site Hernia in Adult - Case Report and Review of Literature - Irpatgire, Ravindra; Vikram, Sarda; Kale, Dinkar (International Journal of Medical Research and Review, 2016)
Hernia is a very common surgical problem.Drain site hernias are very rare (0.1-3.4 %) incidence quoted in literature. We report the case of a 40year old male who presented with a swelling in the right lower abdomen.CT scan revealed herniation of small bowel with interstitial spread through a former drain site placed after a previous laparotomy 10 years back.